1993
DOI: 10.2307/3283383
|View full text |Cite
|
Sign up to set email alerts
|

Mutants of Toxoplasma gondii Resistant to Atovaquone (566C80) or Decoquinate

Abstract: Mutants of Toxoplasma gondii resistant to drugs that appear to affect the mitochondrial bc1 complex were isolated with the aid of mutagenesis with ethylnitrosourea. Mutant DeqR-1 was > 1,000-fold more resistant to decoquinate than was the wild type but more sensitive to atovaquone (formerly called 566C80). Mutant AtoR-1 was 20-fold more resistant to atovaquone than was the wild type and was also partially cross-resistant to decoquinate. Both drugs rapidly inhibited oxygen uptake by freshly prepared extracellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
26
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 16 publications
6
26
0
Order By: Relevance
“…Other authors arbitrarily used an eightfold increase in the inhibitory concentration compared to that of sensitive strains (15). For SDZ and atovaquone, no criterion has been defined, but resistant mutants obtained by mutagenesis have IC 50 s that are 20-to 300-fold higher than that of the wild type (6,38,39).…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors arbitrarily used an eightfold increase in the inhibitory concentration compared to that of sensitive strains (15). For SDZ and atovaquone, no criterion has been defined, but resistant mutants obtained by mutagenesis have IC 50 s that are 20-to 300-fold higher than that of the wild type (6,38,39).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Up to now, very few data document the two latter hypotheses. Drug-resistant mutants have been obtained in vitro by mutagenesis under drug pressure for sulfonamides (38), pyrimethamine (41,42), and atovaquone (32,39). However, the demonstration of a mutation responsible for substantial resistance to sulfonamides was demonstrated for only one clinical isolate (6).…”
mentioning
confidence: 99%
“…However, to date, insufficient passage through the blood-brain barrier (BBB) and/or insufficient bioavailability of these drugs has limited their in vivo use. The hydroxynaphthoquinone atovaquone is a potent inhibitor of the respiratory chain of parasites (17,38) and is used for patients with Pneumocystis carinii pneumonia (46). It has potent in vitro activity against both the tachyzoite and cyst forms of T. gondii (2,24).…”
mentioning
confidence: 99%
“…It has also been suggested that the plastid-like organelles that occur in apicomplexan parasites (13)(14)(15), which have received considerable attention recently (16,17), may contain components of a respiratory chain (18), which could contribute to the respiration of the cell (12). Although the importance of the respiratory chain in T. gondii is unknown, it is thought that it is the target of the anti-Toxoplasma activity of the naphthoquinone atovaquone (19,20), which is currently used against toxoplasmosis in AIDS patients (19).…”
mentioning
confidence: 99%
“…Given the lack of information on mitochondrial physiology in T. gondii and the apparent relevance of mitochondrial activity for its differentiation (7,8) and for the chemotherapy of toxoplasmosis (19,20), it is extremely important to develop strategies to study the mitochondrial bioenergetics of these cells. In this work we report that the use of tachyzoites permeabilized with digitonin, a procedure previously established to investigate in situ mitochondrial bioenergetics in trypanosomatids (25)(26)(27)(28), allowed for the first time the functional characterization of the respiratory chain of an apicomplexan parasite.…”
mentioning
confidence: 99%